PENGARUH EDUCATIONAL TOURISM EXPERIENCE TERHADAP KEPUASAN WISATAWAN DI KAMPUNG BATU MALAKASARI - Hasdian, Adi; Setiyorini, Heri Puspito Diyah (Universitas Pendidikan Indonesia, 2016)
Kampung Batu Malakasari is one of the main tourist destinations located in Bandung. The destination has interesting attractions and activities, where tourists not only traveled for leisure, but get educational value as well. There are also educational tour packages for tourists groups; especially schools that want to get learning experience. In 2014, the number of group of tourists who visited Kampung Batu Malakasari decreased by 10.83%. Moreover, based on the pre-research on 30 respondents who was conducted in 2015, it was found that tourist satisfaction was low, particularly the satisfaction at the educational experience. The guest comments that were compiled by the management have also shown the similar result. In fact, the management already had a great effort in conducting activities in delivering a good educational experience. Hence, it is important to carry out research to discover the influence of the education experience for the tourist's satisfaction at Kampung Batu Malakasari. The independent variable in this research was educational tourism experience (X) that consisted of attractions and events, resource specialists, affinity travel planner's tour and receptive operators. The dependent variable was the touristsâ€™ satisfaction (Y), which was the ratio of the value perceived with the value expected. The approach used for this research was a quantitative method by conducting the explanatory survey. The sample used for this research was 100 respondents with the simple random sampling technique. The data analysis and hypothesis testing used for this research is multiple-linear regression analysis. The results showed that the perceived education experience score was 74.06%, while the expected educational experience score is 75.07%. This score indicated that the response of the touristsâ€™ group to educational experience was at the â€œgoodâ€ category. Likewise, the tourist's response group to tourist satisfaction had 99% as the score, where it was categorized as an